A model of perinatal stress and childhood wheezing: ELSPAC‐CZ cohort. Issue 6 (15th March 2021) - Stepanikova, Irena; Thon, Vojtech; Mikes, Ondrej; Klanova, Jana
Abstract: Background: Prenatal origins of wheezing are not fully understood. This study develops a model of mechanisms linking perinatal stress exposure to wheeze phenotypes in children. Methods: Data were obtained from 1880 mother‐child dyads participating in ELSPAC‐CZ birth cohort. Wheeze phenotypes assessed between birth and age 7 years included "never wheeze, " "early‐onset transient (EOT) wheeze, " "early‐onset persistent (EOP) wheeze, " and "late‐onset (LO) wheeze." Prenatal and postnatal stress exposures were assessed in mid‐pregnancy and 6 months after delivery, respectively, using an inventory of 42 life events. Results: In adjusted models, children in the highest tercile (high) versus lowest tercile (low) for prenatal life events had a 38% higher risk of EOT wheeze (relative risk ratio [RRR] = 1.38; 95% confidence interval [CI] = 1.01–1.88; p  = .041) and 50% higher risk of LO wheeze (RRR = 1.50; 95% CI = 1.00–2.25; p  = .047). High versus low exposure to postnatal life events predicted a 60% increase in relative risk of EOT wheeze (RRR = 1.60; 95% CI = 1.17–2.19; p  = .003) and medium versus low exposure was related to an 85% increase in relative risk of EOP wheeze (RRR = 1.85; 95% CI = 1.16–2.95; p  = .010). Lower respiratory tract infections and postpartum depression partially mediated between postnatal life events and any wheeze (indirect effects 1.06, 95% CI = 1.02–1.09, p  = .003 and odds ratio [OR] = 1.08, 95% CI = 1.02–1.15, p  = .012, respectively), while postnatal events mediate for prenatal events (indirect effect OR = 1.11; 95% CI = 1.03–1.18; p  = .005). Conclusions: Exposures to prenatal and postnatal life events are risk factors for the development of wheezing. Prenatal stress contributes to wheeze directly and also through postnatal life events, respiratory infections, and maternal depression.